2021
DOI: 10.1002/er.7423
|View full text |Cite
|
Sign up to set email alerts
|

Study on the optimum orientation of bifacial photovoltaic module

Abstract: The idiosyncrasy of bifacial photovoltaic devices by means of its ambivalent nature in absorbing irradiation demarcates this technology from conventional monofacial modules. The performance of bifacial PV devices is primarily a function of the orientation of the device, that is, its tilt angle (β), the elevation of the module above the ground (E), the albedo of the location (ρ g ) and the azimuth angle (γ). The current work, focusing on determining the optimum setting for module installation, takes into consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The concepts proposed in Figure 1 to obtain maximal energy in both cases of direct illumination and scattered illumination conditions using bifacial solar cells are supported by the results of previous studies on monofacial solar cells and by the additional power gain of bifacial solar cells at various angles under different illumination conditions ( Younas et al., 2019 ; Yun et al., 2020 ; Raina et al., 2021 ; Bernardi et al., 2012 ; Cui et al., 2019 ; Huang et al., 2020 ). These previously reported results—where the angled alignment of monofacial modules or arrays has been shown to affect the energy yield and where a vertical array of PV modules has been shown to produce more energy under scattered light conditions such as cloudy days by capturing other forms of incident light—have been expanded in the present work to a bifacial solar cell to confirm the effect of its angled alignment under a scattered- and diffused-light environment ( Tayagaki and Yoshita, 2022 ; Yin et al., 2021 ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The concepts proposed in Figure 1 to obtain maximal energy in both cases of direct illumination and scattered illumination conditions using bifacial solar cells are supported by the results of previous studies on monofacial solar cells and by the additional power gain of bifacial solar cells at various angles under different illumination conditions ( Younas et al., 2019 ; Yun et al., 2020 ; Raina et al., 2021 ; Bernardi et al., 2012 ; Cui et al., 2019 ; Huang et al., 2020 ). These previously reported results—where the angled alignment of monofacial modules or arrays has been shown to affect the energy yield and where a vertical array of PV modules has been shown to produce more energy under scattered light conditions such as cloudy days by capturing other forms of incident light—have been expanded in the present work to a bifacial solar cell to confirm the effect of its angled alignment under a scattered- and diffused-light environment ( Tayagaki and Yoshita, 2022 ; Yin et al., 2021 ).…”
Section: Resultssupporting
confidence: 67%
“…To obtain high energy yield from PV systems in an urban environment, many researchers have proposed many solar cell technologies, including organic solar cells ( Zhang et al., 2021 ; Liu et al., 2022 ) and at the same time, improved conventional silicon-based solar cells to bifacial structures to capture direct light, diffused light, and albedo reflected light. These technologies are based on the concept of a stand-alone bifacial module, an east–west-facing vertical module, and a module tilted at an optimized angle ( Baumann et al., 2019 ; Jang and Lee, 2020 ; Nussbaumer et al., 2020 ; Patel et al., 2019 , 2021 ; Raina et al., 2021 ). However, to attain maximum energy yield in a directly illuminated environment, a solar cell module should face the direction of incident light.…”
Section: Introductionmentioning
confidence: 99%
“…This self-shade is dependent on the height of the module from the ground. 39,40 In case of an array, an additional shading scenario may be created if the rows are not optimally spaced. The module in the back row may contribute to the overall reflected radiation incident on the rear of a module placed in the front row.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐uniformity may also arise due to self‐shade from a module, that is, the shade of the module on the ground may reduce the area for direct reflection of incident irradiance on the ground. This self‐shade is dependent on the height of the module from the ground 39,40 . In case of an array, an additional shading scenario may be created if the rows are not optimally spaced.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that tilt angle optimization can significantly increase the solar irradiance incident on panels, which subsequently provides greater solar to electricity conversion [6][7][8]. Raina et al [6] found that a bifacial photovoltaic module installed at an optimum orientation could collect up to 84.76% more irradiance.…”
Section: Introductionmentioning
confidence: 99%